The mechanisms of Huangqi Guizhi Wuwu decoction in treating ischaemic stroke based on network pharmacology and experiment verification - Weiguo Liao; Minchun Wang; Ying Wu; Jinyan Du; Yaxin Li; Anyu Su; Lanying Zhong; Zi Xie; Mingyu Gong; Junhui Liang; Pengcheng Wang; Zai Liu; et al. (Taylor & Francis Group, 2023)
AbstractContext Huangqi Guizhi Wuwu Decoction (HGWD) is effective in treating ischaemic stroke (IS). However, its mechanism of action is still unclear.Objective Network pharmacology integrated with in vivo experiments were used to clarify the underlying mechanisms of HGWD for treating IS.Materials and methods TCMSP, GeneCards, OMIM and STRING were used to retrieve and construct visual protein interaction networks for the key targets. The AutoDock tool was used for molecular docking between key targets and active compounds. The neuroprotective effect of HGWD were verified in a middle cerebral artery occlusion (MCAO) model rat. The Sprague-Dawley (SD) rats were divided into sham, model, low-dose (5 g/kg, i.g.), high-dose (20 g/kg, i.g.), and nimodipine (20 mg/kg, i.g.) groups once daily for 7 days. The neurological scores, brain infarct volumes, lipid peroxidation, inflammatory cytokines, Nissl bodies, apoptotic neurons, and signalling pathways were all investigated and evaluated in vivo.Results Network pharmacology identified 117 HGWD targets related to IS and 36 candidate compounds. GO and KEGG analyses showed that HGWD anti-IS effects were mainly associated with PI3K-Akt and HIF-1 signalling pathways. HGWD effectively reduced the cerebral infarct volumes (19.19%), the number of apoptotic neurons (16.78%), and the release of inflammatory cytokines, etc. in MCAO rats. Furthermore, HGWD decreased the levels of HIF-1A, VEGFA, Bax, cleaved caspase-3, p-MAPK1, and p-c-Jun while increasing the expression of p-PI3K, p-AKT1, and Bcl-2.Discussion and conclusion This study initially elucidated the mechanism of HGWD anti-IS, which contributed to the further promotion and secondary development of HGWD in clinical practice.